2020
DOI: 10.1002/app.49222
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐high compression and wear resistant hybrid filled polyimide composite: Synergistic effect of Fe2O3 decorated RGO

Abstract: Herein, the tribological performance, thermal and compression resistance behavior of polyimide (PI) reinforced by Fe2O3 decorated reduced graphene is systematically investigated. The remarkable synergistic effect of Fe2O3 decorated reduced graphene oxide (RGO) is demonstrated in its PI wear resistance, and PI/RGO/Fe2O3 composites show good thermal stability and much higher compression resistant ability than PI, PI/RGO, and PI/Fe2O3 composites when the filling contents are same. Additionally, the PI/RGO/Fe2O3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The obtained excellent mechanical and tribological properties were attributed to the structure of the composites and chemical bonds between RGO and TiO 2 , which were assumed to prevent the crack propagation under friction conditions and cause the WR reduction, according to Figure 14 (PI; B-o-R; counterpart is a steel; R a = 0.3–0.5 μm; RT; V = 42 cm/s, P = 100–300 N) . Liu, H., et al studied the influence of reduced graphene oxide (RGO) particles decorated with Fe 2 O 3 ones [ 92 ]. Their incorporation in the PI matrix greatly enhanced the antiwear ability of the polymer films.…”
Section: Line Contactsmentioning
confidence: 99%
“…The obtained excellent mechanical and tribological properties were attributed to the structure of the composites and chemical bonds between RGO and TiO 2 , which were assumed to prevent the crack propagation under friction conditions and cause the WR reduction, according to Figure 14 (PI; B-o-R; counterpart is a steel; R a = 0.3–0.5 μm; RT; V = 42 cm/s, P = 100–300 N) . Liu, H., et al studied the influence of reduced graphene oxide (RGO) particles decorated with Fe 2 O 3 ones [ 92 ]. Their incorporation in the PI matrix greatly enhanced the antiwear ability of the polymer films.…”
Section: Line Contactsmentioning
confidence: 99%
“…The strength of composites with a suitable content of nanoparticles was h that of pure PI matrix. For instance, Liu et al [38] found that the PI/reduced oxide (RGO)/Fe2O3 composites showed a compressive strength of 130.97 MP 35.9% higher than pure PI. Zhao et al [39] fabricated PI/nano-SiO2 composite The strength of composites with a suitable content of nanoparticles was higher than that of pure PI matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [39] fabricated PI/nano-SiO2 composite The strength of composites with a suitable content of nanoparticles was higher than that of pure PI matrix. For instance, Liu et al [38] found that the PI/reduced graphene oxide (RGO)/Fe 2 O 3 composites showed a compressive strength of 130.97 MPa and was 35.9% higher than pure PI. Zhao et al [39] fabricated PI/nano-SiO 2 composites via an in situ polymerization method, in which the compressive strength of the composite with 5 wt.% nano-SiO 2 was 125.51 MPa, which increased by 42.6% compared to the pure PI with a compressive strength of 88.02 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing the tribological aspect, results showed that 0.5 wt% GMS loading resulted in a 25% reduction in the coefficient of friction and 64% reduction in the wear rate. Liu et al 103 examined the effects of Fe 2 O 3 decorated reduced graphene oxide (RGO) on the tribological performance, thermal, and compression resistance behaviour of PI matrix. It was reported that the RGO/Fe 2 O 3 /PI composite, which was prepared by in situ polymerization exhibited better thermal stability and much higher compression resistance in comparison with pure PI.…”
Section: Overview Of Polyimide Matrix Materials For Thermal Mechanica...mentioning
confidence: 99%